2002
DOI: 10.1253/circj.66.668
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Therapy in Japanese Patients With Mechanical Mitral Valves.

Abstract: There are no guidelines for the optimal therapeutic range of anticoagulant therapy in Japanese patients with mechanical heart valves. A total of 214 patients were followed retrospectively after mitral mechanical valve replacement (mean duration of follow-up, 4.8 years; total duration of follow-up, 1,027 patient-years). The target range of the international normalized ratio (INR) for oral anticoagulation was between 1.5 and 2.5. For all patients 10,416 measurements of the INR were obtained during the follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 15 publications
(11 reference statements)
2
26
1
Order By: Relevance
“…1,29) Significance and applications in dental surgery: Continuous oral anticoagulant therapy with warfarin has been used to decrease the risk of thromboembolism for more than half a century. The recent guidelines for anticoagulant therapy recommend that interrupting warfarin treatment for dental or minor surgery is prohibited (class III on guideline).…”
Section: Discussionmentioning
confidence: 99%
“…1,29) Significance and applications in dental surgery: Continuous oral anticoagulant therapy with warfarin has been used to decrease the risk of thromboembolism for more than half a century. The recent guidelines for anticoagulant therapy recommend that interrupting warfarin treatment for dental or minor surgery is prohibited (class III on guideline).…”
Section: Discussionmentioning
confidence: 99%
“…5, 9 Moreover, it has been reported that compared with Europeans, the incidence of thromboembolism is low in Japan, despite the less intensive regimen; 10,11 which indicates that adjusted low-dose warfarin (eg, PT-INR 1.6-2.6) is optimal for prevention of thromboembolism in Japanese patients. 12, 13 Considering these racial differences in the anticoagulation therapy, we attempted to validate the IWPC pharmacogenetic dose algorithm for warfarin in Japanese patients under low-TAKEUCHI F et al…”
Section: Editorial P 850mentioning
confidence: 99%
“…The maintenance dose of warfarin is usually determined by monitoring prothrombin time using an international normalization ratio (INR). An INR of 1.5-2.5 is recommended for Asian populations (Matsuyama et al 2002).…”
Section: Introductionmentioning
confidence: 99%